Dogs vs. humans : a showdown of the senses - Gibeault, Stephanie (Owlkids Books, 2025)
"In showdown of the senses, who do you think would win, dog or human? That is the question being explored in this fun, sense-by-sense look at the ways dogs perceive the world and how it compares to the way we humans do. Over the course of six rounds, the sensory abilities of dogs and humans are playfully pitted against one another, with a final tally provided at the end of each section. (For those who are counting, the last round is a bonus that explores the possibility that dogs have extra senses that we do not. And spoiler alert: they don't--or at least not ones scientists have discovered yet.) The competition comes to a sense-sational conclusion that will please curious readers of both species. (It's a tie.) For each sense, the science behind our differences is clearly explained and often accompanied by an illustration for further clarity. (See for e.g., Who Sees it Better? and Who Smells it Better?) And for added context, the dogs' senses are often explained in evolutionary terms. For instance, when it comes to the sense of touch, a dog's nose can actually feel the body heat of another animal from as far as 1.5 m (5 ft.) away -- about the length of a park bench. Stephanie explains that this ability probably helped dogs' wolf ancestors find the warm bodies of hidden prey when they were hunting. Includes a glossary."--